NASIKH WA AL-MANSUKH - Rahmalia, Anita; Putra, Ridho Pramadya (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2022)
There are two sides to the view of the Al-Qur'an, namely that the Al-Qur'an is a book for Muslims which has no disagreements in it (ikhtilaf) but on the other hand there are verses in the Al-Qur'an which pronounce the nasakh pronunciation, namely in verse 106 Q.S. Al-Baqarah. Because of this, there are differences in the points of view of our ulama into two groups. First, those who accept and provide support for the text which means that in the Qur'an there is an annulment. These scholars include Ibnu Kasir and Ahmad Mustafa al-Maragi. Second, they do not accept nasakh in the sense of canceling the law that Allah directly revealed and they interpret nasakh as the same as takhsis or more specifically. The class of scholars included 'Abd al-Muta'al al-Jabri and Muhammad al-Bahi. So it is not surprising that the discussion related to Nasikh Wa al-Mansukh is an interesting topic to study.